World Bank Group Evolution: Technical fixes or urgently needed reform? - Molinari, Andrea (2023)
Twenty-five years after its last major reform, the World Bank is embarking on a wide review of its mission, operational procedures and financial mechanisms. However, the current proposal runs the risk of failing to deliver the structural changes needed to support borrowing countries amidst global crises, and relies on general technical measures that function as patches favouring the ‘logic’ of the market. In light of the ‘crises of development’, retrogression on global development goals, and threats to the multilateral order, the Roadmap seems an inadequate response.